Voices from death row - Jackson, Bruce, 1936-; Christian, Diane, 1939- (Albany : State University of New York Press, 2022)
"A searing, personal look at conditions on Texas's Death Row--told in the words of the prisoners themselves"--
Death by Texas -- Death row.
Includes index.
JSTOR
Keywords: Death row -- Texas; Capital punishment -- Texas; Death row inmates -- Texas -- Case studies; Quartier des condamnés à mort -- Texas; Peine de mort -- Texas; Condamnés à mort -- Texas -- Études de cas; Capital punishment; Death row; Death row inmates; Texas; Case studies